IMPLEMENTATION OF SHARIA ACCOUNTING FINANCIAL SYSTEM AT DARUL ULUM PETERONGAN ISLAMIC BOARDING SCHOOL, JOMBANG - Intan Khoirotun Nisa'; Annisa Nurul Aini; Dwi Ira Nur Khafidhoh (STAI Sebelas April Sumedang, 2024)
This research was conducted at the Dahrul Ulum Peterongan Jombang Islamic Boarding School on the application of the sharia accounting financial system. This research aims to find out and analyze whether the presentation of financial reports at the Dahrul Ulum Peterongan Jombang Islamic Boarding School is in accordance with the Sharia Accounting Guidelines standards for Islamic Boarding Schools. This type of research uses descriptive qualitative research. This qualitative research is research that is carried out intensively, in detail and in depth on a particular object by studying it as a case and research that provides an overview or summary of the results of the processed data. Based on the results of general research, in general, the presentation of financial reports at the Dahrul Ulum Peterongan Jombang Islamic Boarding School uses a recording system with an application called PesantrenQu which is fully in accordance with Islamic Boarding School Accounting Guidelines standards. This is demonstrated by the presentation of financial reports that are complete and still fully in accordance with generally accepted standard principles in sharia accounting